PENGARUH KOORDINASI KERJA TERHADAP PEGAWAI DI KANTOR CAMAT ULU IDANOTAE KABUPATEN NIAS SELATAN - Novita Erlina Halawa (Universitas Nias Raya, 2024)
The purpose of this study was to determine the effect of work coordination on employee performance at the Ulu Idanotae District Office, South Nias Regency. The type of research used is a causal quantitative type. The source of the data was from employees of the Ulu Idanotae Sub-District Office, South Nias Regency using a questionnaire. The population and sample in this study were all employees at the Ulu Idanotae Sub-District Office, South Nias Regency, consisting of 30 respondents. Data collection techniques are questionnaire techniques and documentation techniques. The data analysis method used is multiple linear regression analysis. Based on the research results of testing the hypothesis with a tcount of 5,824 > ttable of 1.702, it means that there is an effect of work coordination on employee performance in the Ulu Idanotae District Office, South Nias Regency. The suggestions for this research are (1) To improve employee performance, completing tasks is sometimes coordinated in each job, so that organizational goals are achieved optimally. (2) In improving performance in an organization, employees should be obliged to follow the procedures for carrying out research. (3) To maintain comfort between colleagues, employees should establish good communication.